(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: According to the WHO, in 2020, almost 800 women died daily from preventable causes related to pregnancy and childbirth. An estimated 95% of these deaths were in low- and middle-income countries (LMICs). Postpartum hemorrhage (PPH), excessive bleeding after childbirth, is a leading cause of maternal death globally. Of the estimated 95% of maternal deaths in LMIC, an unacceptable 95% were due to PPH. A significant barrier to women receiving PPH treatment is access to quality PPH medicines, which is the basis for reducing maternal mortality. The E-MOTIVE Trial Kenyan hub conducted an online survey on September after the E-MOTIVE trial findings were released. This survey assessed the perception of health care providers’ (HCPs) of the quality of oxytocin in Augmentation of Labour, Active Management of third Third Stage of Labor (AMSTL), including PPH management. Methods: An online survey was conducted using the Survey Monkey platform in Gatundu level 4 hospital, Makindu subcounty hospital, and Vihiga, Embu, Nyeri, and Kakamega county referral hospitals. The survey targeted HCPs working within the respective maternity units. The results were analyzed in Excel. Results: 56 HCPs across the 6 health facilities participated in the survey. On augmentation of labor, Oxymed Medisel and Oxytocin Umedical were perceived to be more effective, while a score of 100% with Curtocin and Oxyt Kilitch were perceived to be very ineffective. On AMSTL, Oxymed Medisel, Syntocinin Norvatis, and Oxytocin Laborate were perceived to be very effective, whereas Curtocin and Oxyt Kilitch were perceived to be very ineffective. On PPH management, Oxytocin Umedical, Syntocinon Norvatis, and Oxytocin Laborate were perceived to be very effective, whereas Curtocin and Oxyt Kilitch were perceived to be very ineffective. Oxytocin Laborate was available across the health facilities, with other brands lacking in some facilities. Conclusion: Access to and availability of quality PPH medicines are key to effectively managing PPH and reducing maternal mortality.